Impact of pediatric tracheostomy on family caregivers’ burden and quality of life: a systematic review and meta-analysis - Win Thu Aung; Natasha Yixuan Ong; Shina Qing Chun Yeo; Nur Syahindah Binti Juhari; Gwyneth Kong; Nicole-Ann Lim; Zubair Amin; Zubair Amin; Yvonne Peng Mei Ng; Yvonne Peng Mei Ng (Frontiers in Public Health)
IntroductionThe incidence of pediatric tracheostomy is on the rise. More children are undergoing tracheostomy at a younger age and living longer and cared for at home. Caring for children with tracheostomy affects the caregivers’ Quality of Life (QOL) and caregiver burden. We undertook a systematic review and meta-analysis to determine the impact of pediatric tracheostomy on caregivers’ QOL and caregiver burden.MethodsWe performed a search for quantitative studies measuring QOL, caregiver burden and related factors such as psychological distress, coping, stress, and financial strain using validated instruments, reported by caregivers of children with tracheostomy. We searched PubMed, Embase, Cochrane Central Register of Clinical Trials, CINAHL, and PsycINFO with the following search terms: “pediatrics,” “tracheostomy,” “quality of life,” “caregivers,” “care burden” from the inception of respective databases to 23rd May 2024. Meta-analysis was conducted using R (version 4.3.1).ResultsTwenty-three studies (1,299 caregivers) were included in systematic review. Seven studies (469 caregivers) using Pediatric Quality of Life Family Integrated Module underwent meta-analysis. The pooled mean total family impact score, parental health-related QOL, family functioning score were 70.29 [95% CI, 61.20–79.37], 69.27 [95% CI, 60.88–77.67], and 72.96 [95% CI, 65.92–80.00] respectively. Other key instruments were the Pediatric Tracheostomy Health Status Instrument and Zarit Burden Interview. Qualitative synthesis identified several risk factors for lower QOL and higher caregiver burden: comorbidities in children, younger age at tracheostomy, need for additional medical equipment, presence of older siblings, higher financial strain, being the sole caregiver or being unmarried, and maternal depression. Caregivers’ QOL correlated positively with coping and negatively with stress which is, in turn, associated with medical complications in the first year and the duration of tracheostomy. About 40% of mothers experienced moderate to severe caregiver burden while caring for their children with tracheostomy and this was significantly correlated with depression. Encouragingly, parents also reported positive experience including closeness of the family, feeling stronger, and having a strong sense of mastery.DiscussionCaregivers of children with tracheostomy experience low QOL and high caregiver burden, which were exacerbated by various medical and psychosocial factors. QOL should be assessed during clinical encounters to identify caregivers who require additional support which includes learning coping and stress reduction strategies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=334457, identifier CRD42022334457.